Effects of AI Based Personalization, Perceived Privacy Risk, and Service Quality on Customer Loyalty in E-Commerce Platform - Wahyudi, Muhammad Aria (Ilomata International Journal of Management, 2026)
The rapid expansion of e-commerce in Indonesia has encouraged platforms to adopt AI-based personalization to enhance customer experience and loyalty. However, privacy concerns and service quality remain critical factors influencing customer retention. This study examines the effects of AI-based personalization, perceived privacy risk, and service quality on customer loyalty in Indonesian e-commerce platforms. Novelty: This study offers a novel contribution by empirically integrating AI-based personalization, perceived privacy risk, and service quality into a single explanatory model of customer loyalty within the Indonesian e-commerce context. A quantitative explanatory approach was employed using a cross-sectional survey of Indonesian e-commerce users (n = 260). Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that AI-based personalization and service quality positively and significantly affect customer loyalty, while perceived privacy risk has a negative effect. Service quality demonstrates the strongest influence on customer loyalty. Customer loyalty in Indonesian e-commerce platforms depends on effective AI personalization supported by high service quality and careful management of privacy risks.